Energy Efficiency in Buildings Through the Application of Phase Change Materials: An In-Depth Analysis of the Integration of Spent Coffee Grounds (SCGs) - Abir Hmida; Fouad Erchiqui; Abdelkader Laafer; Mahmoud Bourouis (Energies)
Energy demand in the building sector has drastically increased due to rising occupant comfort requirements, accounting for 30% of the world’s final energy consumption and 26% of global carbon emissions. Thus, to improve building efficiency in heating and cooling applications, phase change material (PCM)-based passive thermal management techniques have been considered due to their energy storage capabilities. This study provides a comprehensive review of the research on PCM applications, types, and encapsulation forms. Various solutions have been proposed to enhance PCM performance. In this review, the authors suggest new methods to improve PCM efficiency by using the multilayered wall technique, which involves employing two layers of a hybrid bio-composite—specifically, the hybrid hemp/wood fiber-reinforced composite with a polypropylene (PP) matrix—along with a layer of PCM made from spent coffee grounds (SCGs). Previous studies have shown that oil extracted from SCGs demonstrates good thermal and chemical stability, as it contains approximately 60–80% fatty acids, with a phase transition temperature of approximately 4.5 ± 0.72 °C and latent heat values of 51.15 ± 1.46 kJ/kg.